FORMULATION AND EVALUATION OF FLOATING MATRIX PELLETS OF MONO AMMONIUM GLYCYRRHIZNATE FOR TREATMENT OF GASTRIC ULCER - EESAA , BILAL KHUDHUR (International Journal of Psychosocial Rehabilitation, 2020)
The main aim of present investigation was to formulation and optimization of sustained release matrix pellets of Mono ammonium glycyrrhizinate. Results: From several tests performed on the formation of pellets it was concluded that each of the factors had a significant effect on preparation of pellets by extrusionspheronization method like diluent (F 1) It was found that Lactose (250mg) shows Uniform size, Spherical shape, Good Strength from morphologystudythanpolymer (F4) It was found that Hydroxy propyl methyl cellulose K15M (100mg) shows Uniform size, Spherical shape, Good Strength. Conclusion: Maintain the sustained release for treatment of ulcer for prolong period of time.